Cost-effectiveness of adding empagliflozin to the standard therapy for Heart Failure with Preserved Ejection Fraction from the perspective of healthcare systems in China - Jiang, Yaohui; Xie, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: The Empagliflozin Outcome Trial in Patients with Chronic Heart Failure with Preserved Ejection Fraction(EMPEROR-Preserved) is the first randomized controlled trial to provide promising evidence on the efficacy of adding empagliflozin to the standard therapy in patients with Heart Failure with Preserved Ejection Fraction(HFpEF), but the cost-effectiveness of add-on empagliflozin treatment remains unclear. Method：A Markov model using data from the EMPEROR-Preserved trial and national statistical database was constructed to assess lifetime costs and utility from a healthcare system perspective. The time horizon was 10 years and a 5% discount rate was applied. Incremental cost-effectiveness ratio (ICER) against willingness to pay (WTP) threshold was performed to evaluate the cost-effectiveness. A series of sensitivity analyses was applied to ensure the robustness of the results. Results：Compared to standard therapy, the increased cost of adding empagliflozin from $4,645.23 to $5,916.50 was associated with quality-adjusted life years (QALYs) gain from 4.70 to 4.81, projecting an ICER of $11,292.06, which was lower than a WTP threshold of $12,652.5. Univariate sensitivity analysis revealed the parameters with the largest impact on ICER were the cardiovascular mortality in both groups, followed by the cost of empagliflozin and the cost of hospitalization for heart failure. Probabilistic sensitivity analysis indicated that when the WTP threshold was $12,652.5 and $37,957.5, the probability of being cost‑effective for adding empagliflozin was 52.7% and 67.6% respectively. Scenario analysis demonstrated that cost of empagliflozin, the cost of hospitalization for heart faliure, NYHA functional class and time horizon had a greater impact on the ICER. Conclusion：At a WTP threshold of $12,652.5, the add-on empagliflozin treatment for HFpEF was cost-effective in healthcare systems in China, which promoted the rational use of empagliflozin for HFpEF.